Resilience: the Future of Civil Protection - Toseroni, Fulvio (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The term Resilience was adopted by Civil Protection in 2009, thanks to the United Nations International Strategy for Disaster Reduction (UN-ISDR), which defined Resilience as “the ability of a system, community or society exposed to hazards to resist, absorb,accommodate to and recover from the effects of a hazard in a timely and efficient manner, including through the preservation and restoration of its essential basic structures and functions.” (ISDR, 2009)." The contribution investigates the roots of the Term Resilience and its conceptual evolution, highlighting how this evolution would contribute to the innovation, also in Italy, of the System of Civil Protection.